Research on Basketball Sports Training Based on Virtual Reality Technology. Issue 3 (August 2021) - Li, Haifu
Abstract: Physical education is an important part of teaching content, and basketball is an important part of physical education. Taking the effective way carries on the basketball sports training, may improve the student's physical quality effectively. This paper first explains the concept of virtual reality technology and the necessity of simulation technology, and at the same time the application of virtual reality basketball teaching. And the research of fixed-point shooting based on virtual reality technology is discussed for readers' reference.